2016
DOI: 10.1038/srep37782
|View full text |Cite
|
Sign up to set email alerts
|

Novel recombinant papillomavirus genomes expressing selectable genes

Abstract: Papillomaviruses infect and replicate in keratinocytes, but viral proteins are initially expressed at low levels and there is no effective and quantitative method to determine the efficiency of infection on a cell-to-cell basis. Here we describe human papillomavirus (HPV) genomes that express marker proteins (antibiotic resistance genes and Green Fluorescent Protein), and can be used to elucidate early stages in HPV infection of primary keratinocytes. To generate these recombinant genomes, the late region of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Cells cotransfected with the wild-type HPV18 genome and the pCpGneo URR (7112) plasmid gave rise to robust colonies after selection in G418. We showed previously that the formation of robust, expanding colonies reflects stable maintenance replication of recombinant HPV18 marker genomes ( 29 ). Therefore, primary keratinocytes were cotransfected with the wild-type HPV18 genome and the series of pCpGneo replicons shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells cotransfected with the wild-type HPV18 genome and the pCpGneo URR (7112) plasmid gave rise to robust colonies after selection in G418. We showed previously that the formation of robust, expanding colonies reflects stable maintenance replication of recombinant HPV18 marker genomes ( 29 ). Therefore, primary keratinocytes were cotransfected with the wild-type HPV18 genome and the series of pCpGneo replicons shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3A ). We previously showed that the Neo R expression cassette derived from this plasmid can be inserted into the late region of the HPV18 genome (replacing the ΔLR deletion described above) to generate a “marker genome” ( 29 ). These marker genomes are able to persistently and stably replicate in keratinocytes, demonstrating that the vector components are not detrimental to viral DNA replication and persistence ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HPV is also known to interact with the tetraspanins CD63 and CD151 to gain cellular entry . After infection, the HPV viral genome must amplify to a low copy number as stable or episomal extra chromosomal elements . The episomal form acts as a reservoir in infected cells, which are morphologically indistinguishable from non‐infected cells, and is responsible for the latent status of infection .…”
Section: Pathogenic Mechanism Of Papilloma Virus Infectionmentioning
confidence: 99%
“…differentiation). Quasivirus particles (recircularized viral genomes packaged in a cell line overexpressing the capsid proteins) can be used to generate papillomavirus and polyomavirus particles to study the early stages of infection, and in theory epitope tagged versions of viral proteins could be packaged in these recombinant particles to facilitate their detection and localization (33,34). More efficient methods are also being established to induce the late stages of infection.…”
Section: Molecular and Cellular Proteomics 16 Supplement 4 S67mentioning
confidence: 99%